Mechanical and Physical Properties of Compressed Earth Brick Continues with Quarry Dust as Sand Replacement - Zaulkefeli, Muhammad Aidil Zikri; Burhanudin, Mohd Khairy (Recent Trends in Civil Engineering and Built Environment, 2024)
The global sand issue is a major issue these days, and it has had a significant impact on the world in a variety of ways, including all the industry building.  In terms of cost of materials in concrete mix including coarse aggregate is increasing from year to year. These study objectives are about use the quarry dust to produce brick as sand replacement. By reducing the quarry dust, will definitely bring a good vibe to the environment. For the next objective to determine the optimum content of quarry dust as sand replacement material by percentage 0%, 25% and 50% of quarry dust. In this project, the product based on ratio 1: 4: 4 which is cement, sand and soil and total of 36 pieces of CEB will be design size of 250mm x 125 mm x 100mm. The test conducted on CEB are density test, water absorption and compressive strength have been tested at Laboratory of brick and concrete. However, in this study the finding of compressive strength at CEB of 25 % and 50 % is stronger than control brick following to the BS3921: 1985. Based on to the ASTM 6140 standard, for CEB density value of 25 % and 50 % less than experimental control bricks and for water absorption tests for CEB percentages of 25% and 50% are follow network specifications set in according to ASTM90 Standard which shall not exceed 15%.